The Role of Toastmasters Clubs in Pakistani Universities during COVID-19 to Reduce English as the Second Language (L2) Speech Anxiety among Students - Humaira Irfan; Mirza Zunair Zafar (Linguistics and Literature Review, 2020)
Pakistan has 30 toastmasters clubs that are chartered with toastmasters International, USA. A toastmasters club aims to promote the communication, public speaking, and leadership skills of people to uplift their morale for attaining various beneficial outcomes. The rationale of the study is to determine how toastmasters clubs in Pakistan during COVID-19 lockdown can reduce the English as the second language (L2) speech anxiety and fears of the participants through planned online activities. The authors used the qualitative research method and designed a survey questionnaire consisting of close and open-ended questions to collect data from 23 toastmasters representing two toastmasters clubs established by highly reputed Pakistan’s public and private universities. It is perceived that toastmasters clubs are using innovative and dynamic strategies to produce interactive sessions. However, speakers feel anxiety during the delivery of online speeches and presentations. They practice novel approaches and techniques to overcome their stress. Several new lessons have been acquired from participating in online meetings and contests organized during the COVID-19 pandemic outbreak. It has been found that clubs in Pakistan have rapidly adapted to new situations to maintain regular meetings and activities since lock down. Interestingly, it is discerned that Pakistani toastmasters clubs have made incredible progress during the lockdown and achieved Smedley Distinguished Award. The findings discuss that timely implementation of initiatives to prevail over the challenges emerging from COVID-19 has enhanced the quality of the Pakistani toastmasters clubs. The research recommends that toastmasters’ university activities be used as an effective model to dispel employees’ fears, apprehensions, and anxiety.